Women, wealth, and community in Perpignan, c. 1250-1300 : Christians, Jews, and enslaved Muslims in a medieval Mediterranean town /: Christians, Jews, and enslaved Muslims in a medieval Mediterranean town. (2017) - Unknown
No abstract available